Unified meso-pores and dense Cu2+ sites in porous coordination polymers for highly efficient gas storage and separation. Issue 13 (13th March 2018) - Lyu, Hongliang; Zhang, Qiang; Wang, Yang; Duan, Jingui
Abstract : Unified meso-pores and dense OMSs in PCPs allow high C2-hydrocarbon storage, as well as rapid and efficient C2 H2/4 enrichment from CO2 mixtures at 298 K. Abstract : Unified meso-pores and dense open metal sites (OMS) in porous coordination polymers (PCPs) allow highly promising H2 and C2-hydrocarbon storage, as well as rapid and efficient C2 H2/4 enrichment from CO2 mixtures. The positive function of the OMS, associated with guest thermodynamics, was well revealed by in situ infrared (IR) spectroscopy study.